Respuesta :

First we want to set the equation equal to zero by subtracting 36 from each side...

x^2 + 5x -36 = 0

Now we factor

(x + 9)(x - 4) = 0

Now set each expression equal to zero and solve...

x + 9 = 0              x - 4 = 0
x = -9                    x = 4

Your solution set is

(-9, 4)

Answer: (-9,4)

Step-by-step explanation: First, we set the equation equal to zero by subtracting 36 from both sides to get x² + 5x - 36 = 0.

Next, we factor the left side of the equation

as the product of two binomials.

Since the factors of -36 that add to +5 are +9 and -4,

we have (x + 9)(x - 4) = 0.

This means that either x + 9 = 0 or x - 4 = 0.

Solving each equation from here,

we have x = -9 or x = +4.

So your solution set is (-9,4).

Ver imagen TheBlueFox